A formação continuada de gestores de licitação no Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Gomes, Josenildo Ferreira (2017)
The beginning of the 21st century was marked by the emergence of the knowledge society, bringing about changes in the modes of production of goods and the repositioning of man as the center of organizations. In this context, continuing education has been established as a policy or as an individual and organizational development mechanism, and the promotion of learning processes has been intensified in recent years. In this aspect, the objective of this research is to analyze the continuing education of bid managers of the Federal Institute of Education, Science and Technology of Paraíba (IFPB), based on the following question: how does the process of continuous education of bid managers at IFPB happen? In methodological terms, this is a descriptive and exploratory field research, which uses a quantitative and qualitative approach with bibliographic and documentary procedures. To reach the objectives, a mixed questionnaire was applied (with open and closed questions), organizing data by means of content analysis. The results showed that the IFPB presents the following picture: when placing the civil servants to work in the bidding sector, only 40% received the necessary training to carry out the activities; 53.3% attest that their leaders always encourage continuing education processes and that the IFPB always makes these training available and pays for that. There is not a well-defined planning in relation to the criteria used, however, 66.7% say they are satisfied and / or fully satisfied with the management of continuing education offered by the institution. Between 2011 and 2015, it is noted that 60% of the servers participated in 4 to 10 continuous education processes and only 1 respondent did not participate in these courses. For the managers, we verified that the purpose of the qualification is to acquire knowledge, to improve the performance in the exercise of the jobs, and to have security in performing the bidding work. None of them mentioned that they participated in continuous education processes as a means to gain advantage in progression by qualification or financial incentive to qualification, as it is guaranteed according to Law 11.091/2005. The subjects of this research showed dissatisfaction considering that the institution does not plan by area and does not allocate budget resources specifically for the bidding sector. As a highlighted result, the bid managers affirm that continuing education should be more "continuous", intense, occurring more often within the institution. Thus, it is suggested that the Personnel Management Board of the IFPB formulate a specific training plan for the bidding sector.